Evolution of radionuclide concentration and the radiological hazards in building material: a review - Jameel E. Salman; Nabil M. Hassan (Journal of Taibah University for Science)
Residents are continuously exposed to ionizing radiation emitted from 238U, 232Th and 40K maintained in building materials, which may cause health risks. Hence, these building materials need to routinely monitor. This study reports a building material that poses a radiation risk. A sample of 123 research papers evaluating concentrations of 238U, 232Th and 40K in 7 types of building material from 38 countries was reviewed. This study revealed that granite had the highest concentrations of 238U, 232Th and 40K, whereas the lowest concentration of 238U and 232Th were in marble, while 40K was in gypsum. It was also observed that the granite had higher levels in seven hazard indices: radium equivalent index, gamma index, alpha index, external and internal hazard indexes, absorbed dose rate index and annual effective dose equivalent index than the recommended limits for each index, while the other materials were lower as hierarchal cluster analysis revealed as well.